Enhancing The Performance of WDM-PDM 16-QAM - Alalfi, Raghad Mohammad Fayez; Alsalem, Abdulkareem (Journal of engineering sciences and information technology, 2023)
In this paper, an optical wavelength division multiplexing system using 16-QAM modulation has been proposed, with Gray coding at the transmitter, coherent detection and digital signal processing at the receiver that allow more tolerance for carrier phase noise with compensation of chromatic dispersion and polarization mode dispersion, and enable high spectral efficiency and ability to transmit at high rates. Simulation carried out using Optisystem environment. Performance tested and evaluated using important metrics based on spectral efficiency, BER, capacity, Q-factor and OSNR.WDM-PDM 16-QAM coherent system was designed using 8 channels, with 10 Gb/s rate for each channel and channel spacing of 25GHz gives an optical spectral efficiency of 4b/Hz, with performance tested for a distance of 250 km. The system performance was compared when using Gray coding and differential coding. Gray coding used in transmitters showed better performance compared to differential coding.
Keywords: coherent optical communication system; DSP; WDM; Optisystem